1996
DOI: 10.1161/01.atv.16.10.1285
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Inhibition of Whole-Blood Clot Procoagulant Activity by Inhibition of Thrombus-Associated Factor Xa

Abstract: Progression of arterial thrombosis partly depends on thrombus-associated thrombin and activated factor X (Xa) activity. However, whether Xa or thrombin is the most appropriate target for inhibition of recurrent thrombosis is unknown. This study was designed to determine whether inhibition of Xa results in more sustained attenuation of thrombus-associated precoagulant activity than does inhibition of thrombin. Clots prepared ex vivo from human whole blood and pathological arterial thrombi from patients were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…Our previous findings document the observation that conditions which induce more extensive mural vascular injury and platelet-rich thrombosis (ie, high shear, electrical injury) cause considerably more Xa/Va activity to be associated with the thrombus, leading to marked local generation of thrombin. 4,8,10,11 Persistence of Bound Xa/Va Activity After Arterial Injury Data from previous experimental and clinical studies are consistent with our observation that Xa/Va activity persists for long periods of time after initial arterial injury. For example, using assays similar to those we used, Barry et al 19 have shown that a 2-hour infusion of hirudin attenuates arterial wallassociated thrombin activity at 24 hours but that bound thrombin activity increases by 48 hours.…”
Section: Role Of the Tissue Factor Pathway After Arterial Injurysupporting
confidence: 90%
See 2 more Smart Citations
“…Our previous findings document the observation that conditions which induce more extensive mural vascular injury and platelet-rich thrombosis (ie, high shear, electrical injury) cause considerably more Xa/Va activity to be associated with the thrombus, leading to marked local generation of thrombin. 4,8,10,11 Persistence of Bound Xa/Va Activity After Arterial Injury Data from previous experimental and clinical studies are consistent with our observation that Xa/Va activity persists for long periods of time after initial arterial injury. For example, using assays similar to those we used, Barry et al 19 have shown that a 2-hour infusion of hirudin attenuates arterial wallassociated thrombin activity at 24 hours but that bound thrombin activity increases by 48 hours.…”
Section: Role Of the Tissue Factor Pathway After Arterial Injurysupporting
confidence: 90%
“…These results suggest that the extent of Xa/Va activity after injury in this preparation is substantially less than that we have previously observed associated with arterial thrombi formed in vivo; the thrombi induce clotting in less than 15 minutes under similar conditions. 8,10 However, the importance of bound Xa/Va activity should not be underestimated, because the thrombin elaborated may markedly potentiate thrombosis by activating the coagulation cofactors V and VIII and by activating platelets. 3,7 In our preparation of balloon-induced aortic injury, mural thrombus was not observed, but platelet and fibrin deposition occurred.…”
Section: Role Of the Tissue Factor Pathway After Arterial Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…By the addition of the factor Xa recognition sequence, the fusion protein inhibited thrombin only in the presence of factor Xa. Because this factor is part of the activated clotting system and is an important determinant of the procoagulant activity of whole blood clots and arterial thrombi, 15 the designed fusion protein represents an anticoagulant that promises to be preferentially active at the site where it is needed.…”
Section: Discussionmentioning
confidence: 99%
“…First, factor Xa cleaves at the C-terminus of its recognition sequence (Ile-Glu-Gly-Arg) and thus liberates the free amino-terminus of hirudin. Second, factor Xa is a major part of the activated coagulation system at the site of arterial clots 15 and may therefore allow a preferential liberation of functional hirudin at the clot. Without an activated coagulation system, the fusion protein would be inert.…”
mentioning
confidence: 99%